Remote microphone systems for preschool-age children who are hard of hearing: access and utilization. (3rd April 2019) - Walker, Elizabeth A.; Curran, Maura; Spratford, Meredith; Roush, Patricia
Abstract: Objectives: Children who are hard of hearing (CHH) have restricted access to auditory-linguistic information. Remote-microphone (RM) systems reduce the negative consequences of limited auditory access. The purpose of this study was to characterise receipt and use of RM systems in young CHH in home and school settings. Design: Through a combination of parent, teacher, and audiologist report, we identified children who received RM systems for home and/or school use by 4 years of age or younger. With cross-sectional surveys, parents estimated the amount of time the child used RM systems at home and school per day. Study Sample: The participants included 217 CHH. Results: Thirty-six percent of the children had personal RMs for home use and 50% had RM systems for school. Approximately, half of the parents reported that their children used RM systems for home use for 1–2 hours per use and RM systems for school use for 2-4 hours per day. Conclusions: Results indicated that the majority of the CHH in the current study did not receive RM systems for home use in early childhood, but half had access to RM technology in the educational setting. High-quality research studies are needed to determine ways in which RM systems benefit pre-school-age CHH.